Odpowiedź :
Odpowiedź:
[tex]d)\ \ ((-3-7)+5):\frac{1}{5}=(-10+5)\cdot5=-5\cdot5=-25\\\\e)\ \ (5-(-2))\cdot\frac{1}{2}=(5+2)\cdot\frac{1}{2}=7\cdot\frac{1}{2}=\frac{7}{2}=3\frac{1}{2}\\\\f)\ \ ((-3-7)+5)\cdot\frac{1}{5}=(-10+5)\cdot\frac{1}{5}=-\not5\cdot\frac{1}{\not5}=-1\\\\g)\ \ \frac{5-(-2)}{2}=\frac{5+2}{2}=\frac{7}{2}=3\frac{1}{2}\\\\h)\ \ \frac{-3-7+5}{5}=\frac{-10+5}{5}=\frac{-5}{5}=-1\\\\i)\ \ -\frac{-12-3+7}{4}=-\frac{-15+7}{4}=-\frac{-8}{4}=-(-2)=2[/tex]
Odpowiedź:
d) ( (-3 - 7) +5 ) : 1/5= ( - 10+5 ) : 1/5= - 5 * 5= - 25
e) ( 5 - (-2 ) )*1/2= ( 5 +2) *1/2= 7*1/2= 7/2= 3 i 1/2
f) ( ( -3-7)+5) *1/5= (-10+5) *1/5= -5 *1/5 ( skracamy 5 i 5 przez 5)= -1 *1= - 1
g) 5- (-2) /2= 5+2 /2= 7/2= 3 i 1/2
h) -3-7 +5 /5= -10+5 /5= -5/5= - 1
i) -12 - 3 +7 /4= -15+7 /4= -8/4= - 2
Szczegółowe wyjaśnienie: